2019
DOI: 10.1186/s12967-019-2049-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration analysis for novel lncRNA markers predicting tumor recurrence in human colon adenocarcinoma

Abstract: Background Numerous evidence has suggested that long non-coding RNA (lncRNA) acts an important role in tumor biology. This study focuses on the identification of novel prognostic lncRNA biomarkers predicting tumor recurrence in human colon adenocarcinoma. Methods We obtained the research data from The Cancer Genome Atlas (TCGA) database. The interaction among different expressed lncRNA, miRNA and mRNA markers between colon adenocarcinoma patients with and without tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…As STK4-AS1 was found to be a cancer "booster" in breast cancer [32], lung cancer [27], and colon cancer [26], we hypothesized that it also promoted the progression of osteosarcoma by p53/p21 pathway. MTT assay with transfected cells revealed that the expression of STK4-AS1 level was associated with cell viability, which was consistent with our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As STK4-AS1 was found to be a cancer "booster" in breast cancer [32], lung cancer [27], and colon cancer [26], we hypothesized that it also promoted the progression of osteosarcoma by p53/p21 pathway. MTT assay with transfected cells revealed that the expression of STK4-AS1 level was associated with cell viability, which was consistent with our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma derives from primitive bone-forming mesenchymal cells [24] and it is also suggested to be regulated by lncRNAs [25]. An increasing number of lncRNAs were identi ed as the prognostic biomarkers or potential therapeutic targets of cancer by bioinformatics study [26,27] and the role of many of them in osteosarcoma has been validated in vivo or in vitro [28][29][30][31]. As the number of lncRNAs is large and the regulation network of lncRNAs is complex, more works are required in this eld.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that long non-coding RNAs (lncRNAs) are RNA molecules with more than 200 nucleotides [ 3 , 4 ]. Generally, lncRNAs modulate the expression level of targeted genes at the post-transcriptional period [ 5 ]. More and more lncRNAs have been found to involve in many aspects of cellular homeostasis, such as angiogenesis, metastasis, cell proliferation, immunity adjustment, genomic stability, and so on [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies about ceRNAs based prediction models of COAD recurrence. In the study of Chen et al, they established ceRNA network for differentially expressed RNAs (DERs) between 15 non-recurrent and 98 recurrent COAD patients from The Cancer Genome Atlas (TCGA) database [16]. Meanwhile, Chen et al identified the prognostic lncRNA markers by using multivariate regression and established a nomogram for recurrence prediction based on the identified lncRNA biomarkers and clinical covariates [16].…”
Section: Introductionmentioning
confidence: 99%